Cultural interchange in adventure education: exploring the interaction of participants and institutional cultures. Issue 1 (2nd January 2021) - Ingman, Benjamin C.
ABSTRACT: This study explores the interaction of participants and institutional cultures in adventure education (AE) through the qualitative method of educational criticism and connoisseurship. Three AE programmes were included in this study: a backpacking expedition (11 participants), a challenge course (29 participants), and a multi-activity adventure programme (21 participants). Through 183 hours of observation and 74 interviews, the thematic categories of cultural rigidity and cultural flexibility were identified. The AE institution exhibits cultural rigidity through guideline enforcement, jargon propagation, and value instillment, which results in participant adaptation. Conversely, the AE institution exhibits cultural flexibility through language accommodation, norm development, and goal setting, which results in participants' ability to sustain selfhood. The implications of these findings include reaffirming the importance of attending to participant experiences in AE and the contention that striking a cultural balance in AE can promote productive cultural interchange as an aim of AE.